(untitled) (Clinics, 2010)
INTRODUCTION: Obesity increases triglyceride levels and decreases high-density lipoprotein concentrations in plasma. Artificial emulsions resembling lipidic plasma lipoprotein structures have been used to evaluate low-density lipoprotein metabolism. In grade III obesity, low density lipoprotein metabolism is poorly understood. OBJECTIVE: To evaluate the kinetics with which a cholesterol-rich emulsion (called a low-density emulsion) binds to low-density lipoprotein receptors in a group of patients with grade III obesity by the fractional clearance rate. METHODS: A low-density emulsion was labeled with [14C]-cholesterol ester and [³H]-triglycerides and injected intravenously into ten normolipidemic non-diabetic patients with grade III obesity [body mass index higher than 40 kg/m²] and into ten non-obese healthy controls. Blood samples were collected over 24 hours to determine the plasma decay curve and to calculate the fractional clearance rate. RESULTS: There was no difference regarding plasma levels of total cholesterol or low-density lipoprotein cholesterol between the two groups. The fractional clearance rate of triglycerides was 0.086 ± 0.044 in the obese group and 0.122 ± 0.026 in the controls (p = 0.040), and the fractional clearance rate of cholesterol ester (h-1) was 0.052 ± 0.021 in the obese subjects and 0.058 ± 0.015 (p = 0.971) in the controls. CONCLUSION: Grade III obese subjects exhibited normal low-density lipoprotein removal from plasma as tested by the nanoemulsion method, but triglyceride removal was slower.